2020
DOI: 10.48550/arxiv.2004.00071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal Health Knowledge Graphs for Patients

Abstract: Existing patient data analytics platforms fail to incorporate information that has context, is personal, and topical to patients. For a recommendation system to give a suitable response to a query or to derive meaningful insights from patient data, it should consider personal information about the patient's health history, including but not limited to their preferences, locations, and life choices that are currently applicable to them. In this review paper, we critique existing literature in this space and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Gyrard et al propose a PKG framework aimed at developing personalized healthcare applications to effectively manage chronic disease ( 8 ). Rastogi and Zaki suggest that PKGs could be used to personalize recommendations from good platforms to encourage a healthy lifestyle ( 9 ). Ammar et al present a mobile health digital intervention that combines both patients’ personal health data and contextual knowledge from various sources ( 10 ).…”
Section: Recent Advancements In Personal Knowledge Graphmentioning
confidence: 99%
“…Gyrard et al propose a PKG framework aimed at developing personalized healthcare applications to effectively manage chronic disease ( 8 ). Rastogi and Zaki suggest that PKGs could be used to personalize recommendations from good platforms to encourage a healthy lifestyle ( 9 ). Ammar et al present a mobile health digital intervention that combines both patients’ personal health data and contextual knowledge from various sources ( 10 ).…”
Section: Recent Advancements In Personal Knowledge Graphmentioning
confidence: 99%
“…The authors incorporate Google Health Knowledge Graph (GHKG) and created a KG that embodies diseases and symptoms and relationships between them. Rastogi et al [50] framed the personal health KG as a combination of context, personalization, and integration with other knowledge-bases. Their study indicated that the literature on personalised health-related KGs is inadequate and lacks a unified standard representation to depict the designated domain.…”
Section: Healthcarementioning
confidence: 99%
“…They define possible classes and relations between entities in a schema. This allows for potentially interrelating arbitrary entities with each other and covers various topical domains [6].…”
Section: Introductionmentioning
confidence: 99%